2001
DOI: 10.1021/ja0027766
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of the Shape Evolution of CdSe Nanocrystals

Abstract: The temporal shape evolution of CdSe quantum confined nanorods (quantum rods) in nonaqueous solvents with organometallic precursors was studied quantitatively and systematically. The experimental results revealed three distinguishable stages in the shape evolution. At high monomer concentrations, nanocrystals grow exclusively along the c-axis of the wurtzite structure, making this axis the long axis of the rods. At intermediate concentrations, nanocrystals grow simultaneously in three dimensions. At low monome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

81
1,907
2
10

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 1,707 publications
(2,041 citation statements)
references
References 31 publications
81
1,907
2
10
Order By: Relevance
“…In our investigation, size focusing and existence of nearly monodispersed, fully grown CdSe nanocrystals also indicates that the formation process did not follow Ostwald ripening growth (i.e., defocusing and broad size distribution), but rather maintained a diffusion-controlled process (size-focusing) 55,57,59 as a form of the livingpolymerzation model.…”
Section: Investigation Of Thementioning
confidence: 61%
“…In our investigation, size focusing and existence of nearly monodispersed, fully grown CdSe nanocrystals also indicates that the formation process did not follow Ostwald ripening growth (i.e., defocusing and broad size distribution), but rather maintained a diffusion-controlled process (size-focusing) 55,57,59 as a form of the livingpolymerzation model.…”
Section: Investigation Of Thementioning
confidence: 61%
“…Peng & Peng observed that the reaction solvent strongly affected synthesis kinetics. 13 Early theoretical studies of nanocrystal growth rates emphasized Ostwald ripening, [14][15][16][17] whereby larger particles grow and smaller particles dissolve, thus widening particle size distributions when reactants are scarce. Researchers concluded that narrower size distributions could be achieved when nanocrystal growth was limited by diffusion rather than by reaction rate.…”
mentioning
confidence: 99%
“…Instead, an excited but electrically neutral state, called and exciton 4 , is created which requires additional energy (E B ) to separate into charge carriers [38,41]. This energy is gained form the offset of energy states at the heterojunction [41][42][43][44][45][46]. Figure 7 gives a ba di ram for the p-n rmed in an inorganic/organic PV cell.…”
Section: Inorganic and Organic Semiconductors Lar Cell Would B Affectmentioning
confidence: 99%